Network design approaches and tradeoffs in QoS route selection with diverse objectives and constraints - Kant, L.; Manousakis, K.; McAuley, A.; Graff, C. (MILCOM 2008 - 2008 IEEE Military Communications Conference, 2008)
Future force networks such as FCS and WIN-T are anticipated to support a wide spectrum of applications with stringent and diverse quality of service (QoS) constraints. While many QoS control mechanisms are being designed, judicious multi-metric QoS route selection mechanisms are often put forth as a key means to help provide QoS assurances. QoS routing based on multiple metrics can potentially provide paths that simultaneously trade off multiple, diverse and conflicting performance requirements. This paper describes the incorporation of flexible and scalable QoS path selection heuristics into a network engineering design analytic toolset (NEDAT). NEDAT is equipped with performance metrics for evaluating the tradeoffs and effectiveness of QoS routing subject to the characteristics of network environments of interest. Using NEDAT we show networks: (a) where QoS routing is very beneficial and (b) where benefits are so small that it in not worth the added computational and bandwidth costs.